VOCABULARY LEARNING STRATEGY EMPLOYED BY HIGH-ACHIEVER UNIVERSITY STUDENTS AT MALANG - Putri, Zizhi Meyretha; Wahyuni, Erly (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
Learners should learn English language basic skills and also the components such as grammar, pronunciation, and vocabulary. The learners will have a difficulty in understanding interlocutor’s mean or expressing their ideas without having a sufficient vocabulary. In learning vocabulary, students may have various strategies used to improve their vocabulary. High-achiever students are considered as students who perform well in school and have a high academic achievement. This research is conducted to find out the most common strategy in learning vocabulary used by high achiever students and the reasons in choosing the strategy. Mixed methods, which combine quantitative and qualitative research design was applied for this research. Then, the instruments of this research are questionnaire and interview. The researcher takes seventh-semester high-achiever students as population and 26 high-achiever students who have Grade Point Average (GPA) 3, 51 - above were taken as the sample of this research. The result showed that the most common strategy employed by high-achiever student is cognitive strategy with mean score of 79.8. The strategies involved were note-taking, highlighting, analyzing, dictionary-use, etc. The high-achiever students preferred to use cognitive strategy because it helped them in learning English skill, easy to apply, to make them speak English well, effective and also it is comfortable to use during learning process Therefore, appropriate learning strategies would help the students perform their English well.